Pengaruh Stres Kerja dan Kepuasan Kerja terhadap Turnover Intention Karyawan pada CV Margo Utomo - Ramadhan, Mochammad Raihanditya; Retno Adiwati, Mei (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
Employees are an important asset for a company, who act as actors to support the achievement of an organization's goals. The existence of employees in a company really needs to be managed and regulated well in order to make a positive contribution to the progress and sustainability of an organization. This research aims to determine and analyze the influence of work stress and job satisfaction on employee turnover intention at CV Margo Utomo. The population in this study were all employees of CV Margo Utomo and sampling in this study used a non-probability sampling method with a total of 60 respondents. The measurement scale uses a Likert scale. The data used in this research is primary data, by distributing questionnaires to the entire sample. The analysis technique used is PLS (Partial Least Square) to see the causal relationship between variables. The test results show that work stress contributes to turnover intention and job satisfaction contributes to employee turnover intention at CV Margo Utomo.